QUY LUẬT DI TRUYỀN GLUTELIN TRONG HẠT LÚA TRỒNG (ORYZA SATIVA L.) - Phượng, Phạm Văn; Hirata, Yutaka (Tạp chí Khoa học Đại học Cần Thơ, 2004)
abstract Improving nutritive quality of rice is very important for developing countries. Glutelin is one major component of protein content in rice grain because it contains 80% of storage protein total (Juliano 1972). In 2002 the six crosses were initially carried out to get at least 15 F1 grains, then propagated to get F2 grains for SDS-PAGE protein electrophoresis. 200 F2 grains per cross were analyzed. Results showed that the inheritances of proglutelin and basic glutelin B2 were controlled by a single dominant gene while acidic glutelin A1 was controlled by two independent genes located in two chromosomes. Acidic glutelin A1 was followed by the genetic rule of dominant epistasis (13:3). Title: Inheritance of Glutelin in cultivated rice species (Oryza Sativa l.)